His-Bundle Pacing in a Patient with Transcatheter Aortic Valve Implantation-Induced Left Bundle Branch Block. (23rd August 2018) - Sen, Jonathan; Mok, Michael; Perrin, Mark
Abstract : Transcatheter aortic valve implantation (TAVI) is an effective intervention for severe aortic stenosis in patients at intermediate or high surgical risk, but damage to the native conduction system such as left bundle branch block (LBBB) may offset its benefits. New onset LBBB is associated with a higher risk of cardiovascular morbidity and mortality. His-bundle pacing (HBP) may be useful to treat TAVI-induced LBBB but has yet to be reported. We present the case of a 76-year-old man with severe symptomatic aortic stenosis treated with TAVI. His preoperative electrocardiogram showed sinus rhythm with a narrow QRS complex. Insertion of a CoreValve Evolut R transcatheter aortic valve was uneventful apart from the development of LBBB with a long PR interval. A dual-lead DDD pacemaker was implanted via the left cephalic vein on the following day. HV was mildly prolonged at 60 ms. Capture of the proximal His restored AV synchrony without correction of LBBB. Repositioning of the lead with capture of the left bundle branch enabled complete ventricular resynchronisation with a single lead. Our case demonstrates that LBBB in the setting of TAVI may be corrected by HBP.